Detection and characterization of the Dezidougou virus (genus Negevirus) in mosquitoes (Ochlerotatus caspius) collected in the Republic of Sakha (Yakutia) - Marina A. Stepanyuk; Stanislav S. Legostaev; Kristina V. Karelina; Nina F. Timofeeva; Ksenia F. Emtsova; Olesia V. Ohlopkova; Oleg S. Taranov; Vladimir A. Ternovoi; Albert V. Protopopov; Valery B. Loktev; Victor A. Svyatchenko; Alexander P. Agafonov (Вопросы вирусологии)
Introduction. Monitoring and research on arthropod-borne microorganisms is important. Recently, with the development of next-generation sequencing methods, many previously unknown viruses have been identified in insects.